In Vivo Determination of Effects of Fractions of Chrysophyllum albidum Leaf Extract on Liver Function of Bitis arietans Envenomated Wistar Rats - Eneji Emmanuel A.; Yakubu O. E.; Imo Chinedu (African Journal of Sciences and Traditional Medicine, 2026)
This study investigated the anti-venom potential of solvent-fractionated ethanol leaf extract of Chrysophyllum albidum against Bitis arietans envenomation in Wistar rats, with a particular focus on antioxidant activity and liver function. Ethanol crude extract of C. albidum leaves was subjected to column chromatography using a gradient mobile phase of hexane, chloroform, ethyl acetate, ethanol, methanol, and water, yielding 24 fractions. All fractions were evaluated in vitro for antioxidant and phytochemical properties, and three fractions (F5B, F6A, and F10B), obtained from ethyl acetate/ethanol (100:0 and 50:50) and methanol/H₂O (50:50) solvent systems, were selected for in vivo studies based on their superior antioxidant activities. Sixty Wistar rats were randomly assigned to 12 groups (n = 5), including normal and envenomated controls, a standard anti-venom serum group, and treatment groups receiving different doses and durations of F5B, F6A, and F10B following intraperitoneal administration of 1.25 mL/kg B. arietans venom. Animals in most groups were treated for three days, whereas selected high-dose groups were treated for 14 days to assess sustained pharmacological effects. Blood samples were collected via cardiac puncture for biochemical analysis of liver function markers (ALT, AST, ALP), and liver tissues were harvested for lipid peroxidation, endogenous antioxidant enzyme assays, and histopathological examination. Phytochemical and antioxidant profiling showed that F5B, F6A, and F10B consistently exhibited the highest DPPH and FRAP activities, β-carotene bleaching inhibition, hydrogen peroxide scavenging capacity, and elevated levels of total flavonoids, phenolics, saponins, and tannins relative to other fractions. Envenomation with B. arietans venom significantly (p < 0.05) increased ALT, AST, and ALP levels in the negative control group compared with normal rats, whereas treatment with C. albidum fractions (F5B, F6A, and F10B) and the conventional anti-venom serum reduced these liver enzymes toward normal values. In the 14-day, higher-dose groups, meaningful pharmacological effects were observed, indicating sustained hepatoprotective and anti-venom potential. Overall, the findings suggest that bioactive antioxidant-rich fractions of C. albidum can mitigate venom-induced hepatic dysfunction and support the development of plant-based adjunct therapies for B. arietans envenomation.